Revolutionaries, coercive institutions and the crisis of collaboration in interwar India - Maclean, Kama (The Indian economic and social history review, 2024)
Earlier generations of historians interpreted revolutionary politics of the interwar period within a paradigm of failure, on the basis that it did not bring about an immediate shift in the colonial dominance in South Asia. Following the ‘revolutionary turn’ in South Asian history, scholars have suggested that revolutionary politics needs to be read for the ways in which it shifted mainstream nationalist strategies and influenced other outcomes, both intended and unintended. This article deepens this analysis, by considering an unexplored outcome of the revolutionary politics of the Hindustan Socialist Republican Association (HSRA): its impact on Indians employed in British institutions, especially coercive institutions such as the police and prisons. These employees may not have resigned from their posts, and ultimately these coercive institutions remained coercive and violent at a macro level. However, based on the evidence presented here, it is clear there was a faintly discernible but important micropolitics emerging from within these institutions, which indicates that some exhibited admiration and sympathy for revolutionary prisoners, quietly and surreptitiously working to ameliorate systems of coercion and punishment, in the process undermining coercive institutions from within. Such a reading prompts a rethinking of paradigms of collaborators as colonial enablers, allowing us to see the withdrawal of cooperation with the colonial regime as a process, which becomes perceptible in the context of anticolonial movements in the late interwar period.
First published online October 30, 2024
Gesehen am 05.12.2024